GENDER JUSTICE IN FAMILY COURT PROCEEDINGS: ANALYSING THE PROVISIONS AND PRACTICES UNDER THE FAMILY COURT ACT, 1984 - Singh, Bandana; Mishra, Prakash Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Gender justice in family court proceedings is a critical aspect of ensuring fairness and equality within the legal system. Family courts play a pivotal role in resolving disputes related to marriage, divorce, child custody, and maintenance, among other family matters. These courts handle cases that have a profound impact on the lives of individuals involved, particularly concerning women and their rights within the family structure. Present paper provides an analysis of the background and context of gender justice in family court proceedings, the significance of studying gender justice within the context of the Family Court Act, 1984.